Peculiar Features of Verbal Formulations in School Mathematics (Global Journal of Human-Social Science, 2014)
The article is an exposure to semiotic-symbolic peculiarities of object-based texts which are the definitions in school math, formulations (descriptions) of some facts and operational methods which are under study in secondary schools.
Keywords: semiotic-symbolic peculiarities; object-based texts; definitions; formulations